Post-verbal agreement and obligatory presence of particle to in Polish dual copula clauses - Rafał Jurczyk (LingBaW)
This paper addresses the obligatory particle to in Polish dual copula clauses (DCCs) with post-verbal agreement and two 3rd person nominative expressions with φ-feature(s) mismatch. It argues that to must be present because the syntax cannot successfully establish the φ-Agree relation between T and the post-verbal nominative expression (NPNOM2). Two crucial premises are adopted. One is Zeiljstra’s (2012) Upward Agree which requires i-features to c-command u-features and, hence, necessitates the closest NPNOM to T to SpecTP-move. The other is Vangsnes’s (2002) obligatory TP identification by the Tense- (provided by T) and φ-features (provided by NPNOM controlling agreement) to anchor the subject to the eventuality denoted by the complex predicate Pred’ [be NPNOM2] (Jurczyk 2021). The examination shows that T-NPNOM2 φ-Agree in DCCs under consideration cannot be established as SpecTP-movement of NPNOM2 is illegitimate; NPNOM2 if formally and syntactically part of Pred’ and is also farther from T than NPNOM1, the pre-verbal nominal expression. Consequently, T’s φ-features remain unvalued, which makes TP formally unidentified. However, since some of T’s NPNOM2-specified features are specified as those on NPNOM1, T attracts NPNOM1 to value them whereas features bearing NPNOM2’s specification get valued as default and lexicalised as the least-marked form in terms of feature specification (following Szucsich 2007), i.e., to[i-neut]. It is thus concluded that the obligatory presence of to is a means of formally identifying TP in case any of T’s NPNOM2-specified φ-features cannot be successfully valued by the T-NPNOM2 Agree relation.